Relationship between udder and teat conformations and morphometrics with milk yield in Murrah buffaloes - Poudel, S. P.; Chetri, D. K.; Sah, R.; Jamarkatel, M. (Journal of Agriculture and Forestry University, 2022)
Udder and teat conformations and measurements play a vital role in milk productivity and mastitis resistance in dairy buffaloes. The study was conducted on apparently healthy 24 Murrah buffaloes running on different parities selected from 3 different farms in the Chitwan district of Nepal to find the relation between phenotypic characteristics of udder and milk yield. The shapes of the teat and udder were evaluated by a visual appraisal that revealed 42.7% funnel, 26% bottle, 16.7% cylindrical, 14.6% conical-shaped teats, and 37.5% round, 33.3% bowl, and 16.7% goaty, and 12.5% stepped shaped udders. The average length, width, and depth of the udder were determined as 54.50±0.92 cm, 19.33±0.46 cm, and 27.50±1.10 cm, respectively, while the respective length and diameter of the teat were 8.46±0.17 cm and 3.59±0.07 cm. Within udder quarters, teat length was significantly different (p < 0.05) though the diameter was non-significant. However, the teat length and teat diameter differed along the teat and udder shapes showing the highest measures at bottle-shaped teats and goaty-shaped udder. The average milk yield/day recorded was 5.90±0.36 kg per buffalo. Higher milk yield was observed in the round-shaped udder and conical-shaped teat. The correlation of udder width (r= 0.237, p<0.05) and teat length (r= 0.222, p<0.05) was observed significantly positive but that of teat to floor distance (r= -0.232, p<0.05) was negative with milk yield. Hence, the selection of Murrah buffaloes for milk production traits should consider the dimensions of the teat and udder.